Was weiß YouTube über das „Konzept für feste Dritte Zähne an einem Tag“? - Kurtuluş, İkbal Leblebicioğlu and Eraslan, Ravza and Berger, Lara (Implantologie, 2023)
The aim of the study is to evaluate the popularity, content, validity and didactic quality of information videos on YouTube about the concept of “new teeth in one day” for dentists and lay people. Following a search using Google trends for the most frequently used term for the “new teeth in one day” procedure, the first 150 videos on YouTube were reviewed under the search term “All-on-Four” by two prosthodontics specialists and a layperson. After considering the exclusion criteria, the remaining 85 videos were analyzed, recording the origin and content of the video posts, the number of days since upload, and the number of views, “likes,” and finally “dislikes.” Alongside this, the popularity of the videos was assessed using the video popularity index (VPI). Overall, the popularity, content, reliability, and quality of the information contained in the videos were evaluated. The accuracy and reliability of the information were determined using the adapted DIScERN score. Several scales were used to evaluate the didactic quality of the videos in order to further assess the sub-areas of the quality parameters. These included the Journal of the American Medical Association (JAMA) scales, the modified Global Quality Score (mGQS), and the Total content Score (TcS). The mean scores for the videos were 74.48 for the cPI, 27.50 (low) for the DIScERN, 1.36 for JAMA, 2.25 (medium) for the mGQS, and 2.15 (low) for the TcS. The three observers showed significantly good agreement on all rating scales. Video duration (minutes) showed significant moderate positive correlations with the DIScERN score, the mGQS score, and the TcS. The reliability of YouTube videos on the “new teeth in one day” treatment concept is low, which is why video postings of this topic should not be the primary source of information for either experts or patients.
CRIS-Team Scopus Importer:2023-09-01
Keywords: All on Four; implant-supported immediate restoration; internet; prosthetics; video; YouTube